The "faulkner equation" for predicting body fat: The end of a myth - Maria Fátima Glaner; Cândido Simões Pires Neto (Universidade Federal de Santa Catarina, 2007)
The supposed "Faulkner equation" for estimating relative body fat (F%) has been used with a variety of samples, for both sexes and for differing purposes. Therefore, the goal of this study is to describe certain considerations of a historical nature in order to retrace its introduction and spread in Brazil and to analyze its origin and applicability. There is evidence that this equation was introduced to Brazil by LABOFISE (UFRJ) and LAPEX (UFRGS). It was originated by the combination, which was done by Yuhasz, of the regression and interception coeffi cients and/or standard error of estimation and coeffi cient of determination, of equations developed by Yuhasz, for young men and adults. Hitherto, the "Faulkner equation" should be called the Yuhasz equation (up: unpublished). It was evidenced that Faulkner did not develop any equations for swimmers. The Yuhasz equation (up) may be a good option for estimating F% in young, physically trained men. RESUMO A suposta "equação de Faulkner" para estimar a gordura corporal relativa (G%) tem sido usada em diferentes amostras, para ambos os sexos e com diferentes propósitos. Portanto, este estudo teve por finalidade trazer algumas considerações de cunho histórico para resgatar a sua introdução e divulgação no Brasil e, analisar sua origem e aplicabilidade. Há evidências de que esta equação foi introduzida no Brasil pelo LABOFISE da UFRJ e LAPEX da UFRGS. Sua origem está na combinação, feita por Yuhasz, dos coefi cientes de regressão e intercepções e/ou do erro padrão de estimativa e coefi ciente de determinação, das equações desenvolvidas por ele mesmo, para homens jovens e adultos. Doravante, esta "equação de Faulkner" deve ser chamada de equação de Yuhasz (np: não publicada). Existem evidências que nenhuma equação foi desenvolvida por Faulkner para nadadores. A equação de Yuhasz (np) pode ser uma boa opção para estimar a G% em homens jovens, treinados fisicamente.